Overview of CNM LGAD results: boron Si-on-Si and epitaxial wafers. (1st September 2022) - Grieco, C.; Castillo García, L.; Doblas Moreno, A.; Gkougkousis, E.L.; Grinstein, S.; Hidalgo, S.; Moffat, N.; Pellegrini, G.; Villegas Dominguez, J.
Abstract: Low Gain Avalanche Detectors (LGADs) are n-on-p silicon sensors with an extra p-layer below the collection electrode which provides signal amplification. When the primary electrons reach the amplification region new electron-hole pairs are created that enhance the generated signal. The moderate gain of these sensors, together with the relatively thin active region, provide precise time information for minimum ionizing particles. To mitigate the effect of pile-up at the HL-LHC the ATLAS and CMS experiments have chosen the LGAD technology for the High Granularity Timing Detector (HGTD) and for the End-Cap Timing Layer (ETL), respectively. A full characterization of recent productions of LGAD sensors fabricated at CNM has been carried out before and after neutron irradiation up to 2.5 × 10 15 neq /cm 2 . Boron-doped sensors produced in epitaxial and Si-on-Si wafers have been studied. The results include their electrically characterization (IV and bias voltage stability) and performance studies (charge and time resolution) for single pad devices with a Sr-90 radioactive source set-up. The behaviour of the Inter-Pad region for irradiated 2 × 2 LGAD arrays, using the Transient Current Technique (TCT), is shown. The results indicate that the Si-on-Si devices with higher resistivity perform better than the epitaxial ones.